Heat treatment temperature-induced microstructure, microhardness and wear resistance of Inconel 718 produced by selective laser melting additive manufacturing - KAYNAK, YUSUF (ELSEVIER GMBH, 2021)
Additive manufacturing (AM) has been becoming more widespread and its usage area has been increasing in various industries. However, the mechanical and microstructural properties of the metal parts fabricated by additive manufacturing requires further investigation. In this study, various heat treatment temperature were applied to Inconel 718 specimens fabricated by selective laser melting (SLM) to examine their effects on microstructure, microhardness and wear behavior of the specimens. Moreover, the microhardness and wear response of specimens fabricated by SLM were compared with the wrought Inconel 718. The results provide strong evidence that heat treatment temperature is capable of altering microstructural aspects of as-built specimens. This study also shows microhardness and wear resistance is remarkably induced from the final state of microstructure. Comparative study also provides evidence that Inconel 718 specimen fabricated by SLM can have much higher wear resistance than conventionally produced Inconel 718 if it is heat-treated at certain temperature.
Keywords: Selective laser melting; Heat treatment; Wear behavior; Microstructure; MECHANICAL-PROPERTIES; PARAMETERS; BEHAVIOR; ALLOY